The Effect of Health Education Method Using Printed Booklet Media on Adolescents’ Knowledge Level About Sexually Transmitted Diseases (STDs): A Pre-Experimental Study Among Grade XI Students of SMAN 3 Surabaya, Indonesia - Nolla Aji Maydinanti; Endah Suprihatin; Sari Luthfiyah; Yessy Dessy Arna (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
Sexually Transmitted Diseases (STDs) are one of the reproductive health issues that remain a serious concern among adolescents. Lack of adequate knowladge, taboo perceptions within families, and exposure to unreliable information from the internet increase adolescents’ risk of STDs. Effectife health promotion effort are needed to improve adolescents’ knowladge, one of wich is through the use of educational media that is appropriate for the target audiance. This study aims to analyze the effect of health education using booklets on adolescents’ knwoladge of STDs. This study uses a pre-experimental design with a one-group pretest-posttest approuch. This study sampel consisted of high school students selected using total sampling technique. The intervention consisted of health education using booklets containing material on the definition of STDs, types of STDs, modes of transmission, sign and symptoms, and prevention effort. Data collection was conducted using a knowladge questionnaire administered before and after the intervention. Data analysis was performed using the wilcoxon test. The results showed a significant increase in students’ knowledge levels after receiving education through the booklet, with a p-value < 0.05. The majority of students were in the good knowledge category on the post-test, and no students were found to have poor knowledge. These findings indicate that booklets are effective as a health education tool to increase adolescents’ knowledge about STDs. The use of booklets can be an applicable and sustainable health promotion strategy in school.